Performance-based seismic assessment of a base-isolated bridge-pier - Saritaş, Fevzi (Informa UK Limited, 2019)
AbstractIn structural assessments, plastic strains beyond the elastic limits play an important role in the inelastic responses under seismic effects. In this article, an isolated concrete-pier is a...